The Effectiveness of Using Quizizz Application in Learning English at the Second Grade of SMPN 01 Ponggok - Bahari, Yusuf (Pubmedia Jurnal Pendidikan Bahasa Inggris, 2024)
In language, there are rules that used as guidelines for compiling words into a sentence. In English, the rules that regulate words into the composition of a sentence and have this meaning are called grammar. The benefit of learning grammar which includes part of speech and then apply it is to facilitate the preparation of a correct sentence both orally and written. Learning media will attract students’ attention and increase student learning motivation. The design in this research is experimental research. The subject of this research was 32 students of eight class A and C of SMP Negeri 01 Ponggok. This study used a quantitative approach using a interviews and instruments. The process of treatment by using Quizizz Application as learning media goes through stages as follows: (1) Stage 1: Giving Pre-test, (2) Giving Treatment, (3) Giving Post-test. The research was aimed to find out the whether Quizizz Application effective to enhance students grammar achievement in second grade of SMP Negeri 01 Ponggok, and also to find out the strenght of significance value the effect of Quizizz Application to enhance students grammar achivement in second grade of SMP Negeri 01 Ponggok. The result of the reseach showed that; (1) The applied of Quizizz Application as learning media effectively enhance the students grammar achievement. (2) The significance value of the effectiveness of Quizizz Application as learning media in the amount of 7,025 based on the t-value. Based on the result of research, it can be concluded that the effectiveness of Quizizz Application as learning media towards the english grammar achievement of the second grade students of SMP Negeri 01 Ponggok was effectively to enhance the grammar achievement and show the strenght of significance.